ANALISIS AKUNTABILITAS DAN EKUITAS SYARIAH DALAM PENGELOLAAN BIAYA HUTANG PADA BISNIS SYARIAH - Nur Aidah; Rina Anugra; Masyhuri Masyhuri (Program Studi Akuntansi Syariah, 2025)
This study analyzes the accountability of Sharia and justice in the management of debt costs in Sharia businesses. With the rapid growth of the Sharia industry, the management of debt costs has become an important challenge. This research aims to examine the management of debt costs in Sharia companies from the perspective of equity and accountability. The study employs a literature review approach to identify best practices in debt management that align with Sharia principles. The research findings highlight the importance of transparency and accountability in financial reporting, as well as the need for technology integration to enhance efficiency. Alternative financing approaches such as mudarabah, musyarakah, and murabahah are proposed as solutions to comply with Sharia law.